Comprehensive Clinicopathologic and Molecular Analysis of Mast Cell Leukemia With Associated Hematologic Neoplasm: A Report and In-Depth Study of 5 Cases - Li, Philippa; Biancon, Giulia; Patel, Timil; Pan, Zenggang; Kothari, Shalin; Halene, Stephanie; Prebet, Thomas; Xu, Mina L. (Frontiers in Oncology, 2021)
Mast cell leukemia with associated hematologic neoplasm (MCL-AHN) is a rare and highly aggressive entity that remains understudied due to the paucity of cases. We present a case of a 45-year-old man who was concurrently diagnosed with mast cell leukemia and acute myeloid leukemia. We identified four additional patients who had MCL-AHN in our institution and performed whole-exome sequencing of all available tumors. Our series revealed a novel and identical NR2F6 variant shared among two of the patients. This case series and sequencing results demonstrate the importance of fully characterizing rare tumors that are resistant to treatment.